Investigation of choroid plexus variability in schizophrenia-spectrum disorders—insights from a multimodal study - Vladislav Yakimov; Joanna Moussiopoulou; Lukas Roell; Marcel S. Kallweit; Emanuel Boudriot; Matin Mortazavi; Sergi Papiol; Lenka Krčmář; Mattia Campana; Eva C. Schulte; Nicolas Glaichenhaus; Emanuela Martinuzzi; et al. (Schizophrenia)
Abstract Previous studies have suggested that choroid plexus (ChP) enlargement occurs in individuals with schizophrenia-spectrum disorders (SSD) and is associated with peripheral inflammation. However, it is unclear whether such an enlargement delineates a biologically defined subgroup of SSD. Moreover, it remains elusive how ChP is linked to brain regions associated with peripheral inflammation in SSD. A cross-sectional cohort of 132 individuals with SSD and 107 age-matched healthy controls (HC) underwent cerebral magnetic resonance imaging (MRI) and clinical phenotyping to investigate the ChP and associated regions. A case-control comparison of ChP volumes was conducted, and structural variance was analyzed by employing the variability ratio (VR). K-means clustering analysis was used to identify subgroups with distinct patterns of the ventricular system, and the clusters were compared in terms of demographic, clinical, and immunological measures. The relationship between ChP volumes and brain regions, previously associated with peripheral inflammation, was investigated. We did not find a significant enlargement of the ChP in SSD compared to HC but detected an increased VR of ChP and lateral ventricle volumes. Based on these regions, we identified 3 clusters with differences in cognitive measures and possibly inflammatory markers. Larger ChP volume was associated with higher volumes of hippocampus, putamen, and thalamus in SSD but not in HC. This study suggests that ChP variability, but not mean volume, is increased in individuals with SSD, compared to HC. Larger ChP volumes in SSD were associated with higher volumes of regions previously associated with peripheral inflammation.